Routes to better partnership: a map of CGIAR research in Africa - International Livestock Research Institute (International Livestock Research Institute, 2009)
The CGIAR research database for eastern and southern Africa is an online project repository of all the CGIAR projects in the region. It answers the question: who is doing what, where and with whom?